Fiscal Policy Reaction Function and Sustainability of Fiscal Policy in Ukraine - Artem Vdovychenko (Visnyk of the National Bank of Ukraine, 2017)
This study analyzes the fiscal policy reaction function with switching regimes. We use Logistic Smooth Transition Regressions (LSTR) to show that fiscal policy in Ukraine during the study period remained largely in passive mode, switching to active mode during periods of a high output gap and elevated debt-to-GDP ratio. An important finding is that the fiscal policy reaction function is nonlinear. Specifically, the response of fiscal policy to the output gap is asymmetric: fiscal policy is pro-cyclical during periods of economic growth but neutral in recession.